Effect of processing on microstructure and mechanical properties of pentaglycerine based solid-solid phase change materials. (25th November 2022) - Serrano, Angel; Garrido, Ignacio; Santos, Sergio; Duran, Mikel; Dauvergne, Jean-Luc; Carmona, Manuel; Palomo Del Barrio, Elena
Abstract: The present work addresses the lack of reported information about the mechanical properties of solid-solid PCMs, and how these are affected by their processing, considering that they usually incorporate fillers to increase their thermal conductivity. To this end, this work analyzes pentaglycerine (PG) based composites, which are of great interest in TES intended for 80 °C. These composites are also doped with various contents of expanded graphite (EG) with two different particle sizes. With these combinations, the effect of two typical processing methods, pressing and casting, on the microstructure of the composites is evaluated. Furthermore, the mechanical behavior of these composites in both crystal and plastic phases, as well as their thermal expansion during the transition process, is also reported in the current study. Besides demonstrating the important role that processing plays in these properties in PG/EG-based composites, it has been found that the use of EG is also beneficial for mitigating the permanent deformations experienced by these composites during thermal cycling. Finally, the exposed results give the first evidence of the interesting effect these processing methods have on the thermal properties of the composites. Highlights: The effect of processing on the structure of PG-EG composites has been explored. Their mechanical properties both at crystal and plastic phases are evaluated. Pressed specimens show better mechanical properties than cast specimens. EG diminishes permanent composite deformation during thermal cycling. Composites manufactured by pressing exhibit less subcooling than cast specimens.